Penerapan School Well-Being Dalam Pendidikan Dasar - Aditya Gunawan (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This study aims to examine the importance of implementing the concept of school well-being in the primary education environment as a fundamental basis for creating a meaningful learning ecosystem. Amidst the global educational paradigm shift, schools are no longer only required to pursue academic mastery but also to ensure students' mental health and happiness. The research method employed is library research with a systematic literature review approach towards eight relevant scientific articles. The findings indicate that school well-being, which encompasses dimensions of school conditions (having), social relations (loving), self-fulfillment (being), and health, contributes significantly to increasing learning motivation, active student engagement, and positive character building. These findings emphasize that a school environment that is emotionally safe and socially supportive can minimize the academic pressure often experienced at the primary education level. In conclusion, the implementation of school well-being requires a holistic approach involving synergy between school policies, curriculum, teachers, and the active role of parents. The integration of these welfare principles is expected to produce a generation that is not only intellectually bright but also emotionally and morally strong.